To share or not to share: communication of caregiver-reported outcomes when a patient has colorectal cancer - A. Fuchsia Howard; María-José Torrejón; Kelsey Lynch; Scott M. Beck; Sally Thorne; Leah Lambert; Antony Porcino; Mary A. De Vera; Janine M. Davies; Jonathan Avery; Angela C. Wolff; Melanie McDonald; et al. (SpringerOpen, 2022)
Abstract Background The importance of patient-centered measurement in cancer care has led to recognition of the potential for caregiver-reported outcomes to improve caregiver, patient and healthcare system outcomes. Yet, there is limited evidence to inform caregiver-reported outcome implementation. Our purpose was to generate evidence to inform the meaningful and constructive integration of caregiver-reported outcomes into cancer care to benefit caregivers, including exploration of the question of the extent to which these assessments should be shared with patients. We focused on caregivers of patients with colorectal cancer (CRC) because CRC is common, and associated caregiving can be complex. Results From our Interpretive Description analysis of qualitative interview data from 78 participants (25 caregivers, 37 patients, and 16 healthcare providers [HCPs]), we identified contrasting perspectives about the sharing of caregiver-reported outcome assessments with patients with CRC. Those who preferred open communication with both the patient and caregiver present considered this essential for supporting the caregiver. The participants who preferred private communication without the patient, cited concern about caregiver- and patient-burden and guilt. Recognizing these perspectives, HCPs described strategies used to navigate sensitivities inherent in preferences for open versus private communication. Conclusions The integration of caregiver-reported outcomes into cancer care will require careful consideration of caregiver and patient preferences regarding the communication of caregiver assessments to prevent additional burden.